Pengaruh Permainan Educaplay terhadap Kemampuan Membaca Awal di TKIT Asiyah Syifa - Puja Nosarima; Syahrul Ismet; Dadan Suryana; Yul Syofriend (Program Studi Pendidikan Guru Pendidikan Anak Usia Dini, Fakultas Tarbiyah dan Keguruan, Universitas Islam Bandung., 2025)
This study was motivated by the low early reading ability of young children at Aisyiyah Syifa Integrated Islamic Kindergarten in Padang City. This condition was observed during morning journal activities, where many children were unable to recognize letters and could only memorize sound patterns. The study aimed to determine the effectiveness of using the Educaplay game in improving early reading skills among young children. A quantitative approach was employed using a pre-experimental design with a One-Group Pretest-Posttest model. The research subjects consisted of 15 children aged 5 years. Data were collected through early reading ability tests (pre-test and post-test) and analyzed using the Paired Sample t-Test and effect size calculation. The results showed a significant improvement in children’s early reading ability after using Educaplay, with a p-value of 0.000 < 0.05 and a Cohen’s d value of 5.89 (high category). Therefore, the Educaplay game is effective in enhancing early reading skills in young children.